A nationwide analysis of the treatment patterns, survival, and medical costs in Korean patients with relapsed or refractory diffuse large B-cell lymphoma - Cho, Jeong-Yeon; Jang, Suk-Chan; Kang, Dong-Won; Lee, Eui-Kyung; Koh, Hyein; Yoon, Dok Hyun; Park, Mi-Hai (Frontiers in Oncology, 2024)
Background: Approximately one-third of patients with diffuse large B-cell lymphoma (DLBCL) are refractory to treatment or experience relapse after initial therapy. Unfortunately, treatment options for older patients and those who experience relapse or become refractory to hematopoietic stem cell transplantation (HSCT) are limited. This nationwide population-based study aimed to identify treatment patterns, survival times, and treatment costs in patients with relapsed/refractory DLBCL (R/R DLBCL). Materials and methods: Between 2011 and 2020, data on patients with R/R DLBCL were retrieved from the Korean Health Insurance Review & Assessment Service, encompassing the entire population. We identified the treatment patterns for each treatment line using a Sankey diagram and calculated the median time to the subsequent treatment in line. Median overall and progression-free survival times were estimated using the Kaplan–Meier survival curves. Finally, the medical costs incurred during DLBCL treatment were calculated for each treatment line and the costs related to HSCT were summarized at the episode level. Results: A total of 864 patients with R/R DLBCL who received second-line treatment were identified, and a regimen of ifosfamide, carboplatin, and etoposide (ICE) was administered the most. Among them, 353 were refractory or relapsed cases that were treated with third-line treatments. The median times for second-line to third-line, third-line to fourth-line, fourth-line to fifth-line, and fifth-line to sixth-line treatment failures gradually decreased (3.93, 2.86, 1.81, and 1.38 months, respectively) The median overall survival time was 8.90 and 4.73 months following the second-line and third-line treatments, respectively. In the third-line treatment setting, the patients did not show a significant difference in survival time after HSCT. The median medical cost was $39,491 across all treatment lines including the cost of HSCT which was $22,054. Conclusions: The treatment patterns in patients with R/R DLBCL, especially at third-line treatments and thereafter, were complicated, and their prognosis was poor despite the high medical costs. Novel and effective treatment options are expected to improve the prognosis and alleviate the economic burden of patients with R/R DLBCL.